2007
DOI: 10.1016/j.bbrc.2007.07.186
|View full text |Cite
|
Sign up to set email alerts
|

NFATc is required for TGFβ-mediated transcriptional regulation of fibronectin

Abstract: Calcineurin is an important regulator of extracellular matrix (ECM) accumulation in the kidney but functions in a cell-specific manner. Previously, we identified a novel role for calcineurin in mesangial cells where calcineurin activity is required for TGFβ-mediated induction of fibronectin expression. In this study we examined the role of the calcineurin substrate NFATc in transcriptional regulation of fibronectin. First, inhibition of calcineurin blocks TGFβ induction of the fibronectin promoter. Moreover, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 22 publications
4
28
0
Order By: Relevance
“…It should be noted, however, that the response to NFAT activation is highly cell dependent. For example, it was shown that calcineurin/NFAT mediates TGF-␤-induced fibronectin upregulation in glomerular mesangial cells while it has the opposite impact in tubular cells (10). Our results definitively identified NFAT as a stimulant of fibronectin production in podocytes in a TGF-␤-independent manner.…”
Section: Discussionsupporting
confidence: 68%
“…It should be noted, however, that the response to NFAT activation is highly cell dependent. For example, it was shown that calcineurin/NFAT mediates TGF-␤-induced fibronectin upregulation in glomerular mesangial cells while it has the opposite impact in tubular cells (10). Our results definitively identified NFAT as a stimulant of fibronectin production in podocytes in a TGF-␤-independent manner.…”
Section: Discussionsupporting
confidence: 68%
“…These results thus demonstrated that SIRT3 plays a role in regulating the TGF-␤1 signaling. In addition to TGF-␤ signaling, tissue fibrosis can also be promoted by activation of transcription factors like ␤-catenin and NFATc (23)(24)(25)(26). We therefore measured expression of these factors in Sirt3-KO hearts.…”
Section: Resultsmentioning
confidence: 99%
“…Another research found that there is only a small amount of CaN expression in a normal kidney, mainly in renal proximal tubules. 18 Gooch et al 19,20 reported that CaN expression in kidney tissue increased, and the activity of CaN phosphatase also upregulated in the early stage of diabetes. CaN played an important role in glomerulosclerosis of DN, and inhibiting CaN could obviously alleviate the degree of glomerulosclerosis.…”
Section: Discussionmentioning
confidence: 99%